Twenty-First Century Male Elegance Amongst Elegantly-Dressing Polish Males and Self-Declared “Dandies” - Maciejewski Grzegorz; Lesznik Dawid (Marketing of Scientific and Research Organizations, 2021)
Dandyism was a thriving philosophical and social movement amongst elegant men of the nineteenth century. The prevailing conviction in the literature on the subject is that the dandy trend began to gradually disappear in the twentieth century, whereas in the new millennium it essentially no longer exists, or at best exists only as a mere shadow of itself. Herein we report a questionnaire study of elegantly-dressing Polish males regarding their behaviour on the fashion market, seeking to gain an better image of this particular market segment and at the same time to identify the features of contemporary dandies and possible connections with the “metro” style. The results indicate that dandyism (at least in the respondents’ opinion) is still a lively and thriving e-consumer community, which clearly differs in terms of certain features from metrosexualism. However, the modern-day “dandies” cannot easily be considered heirs to the ideals of their nineteenth-century counterparts. Our findings, in particular the characterization of twenty-first-century elegant-dressing men in Poland, may be of use to fashion brands in the broader men’s elegance segment.